Strategic priorities in Portuguese higher education institutions - Mourato, J.; Patrício, M.T.; Loures, L.; Morgado, H. (Studies in Higher Education, 2021)
This paper presents an analysis of strategic management systems of higher education institutions (HEIs) by identifying policy and strategic priorities and monitoring their implementation. The strategic priorities are contextualized within four scenarios that structure the mission and orientation of HEIs. The methodology is based on data collected by a survey to top administrators in Portuguese HEIs. The study identifies and compares the strategic priorities of Portuguese higher education institutions. The top priorities are concern with internationalization and quality assurance, consistent with the rise of quality assurance systems and the growth of international mobility flows. The study also compares the support techniques for monitoring strategic management.